Increased Rate of Pump Thrombosis and Cardioembolic Events Following Ventricular Tachycardia Ablation in Patients Supported With Left Ventricular Assist Devices. Issue 10 (November 2020) - Grinstein, Jonathan; Garan, A. Reshad; Oesterle, Adam; Fried, Justin; Imamura, Teruhiko; Mai, Xingchen; Kalantari, Sara; Sayer, Gabriel; Kim, Gene H.; Sarswat, Nitasha; Raikhelkar, Jayant; Adatya, Sirtaz; et al.
Abstract : Ventricular arrhythmias are common following left ventricular assist device implantation (LVAD), and the effects of ventricular tachycardia (VT) ablation on thrombosis and embolic events are unknown. We aimed to assess LVAD thrombosis, stroke, and embolic event rates after VT ablation. Left ventricular assist device implantation patients from two academic centers who underwent endocardial VT ablation between 2009 and 2016 were compared to a control group with VT who were not ablated and followed for one year. The primary composite outcome was confirmed or suspected LVAD thrombosis, stroke, or other embolic event. Survival analysis was conducted with Kaplan-Meier curves, log-rank tests, and Cox regression. Forty-three LVAD patients underwent VT ablation, and 73 LVAD patients had VT but were not ablated. Patients who were ablated were more likely have VT prior to LVAD ( p = 0.04), monomorphic VT ( p < 0.01), and to be on antiarrhythmics ( p < 0.01). Fifty-eight percent of the patients in the ablation group experienced the primary composite outcome (11% had confirmed device thrombosis [DT], 41% suspected DT, 39% had a stroke or embolic event) compared to 30% in the control group (12% with confirmed DT, 11% with suspected DT, 14% with stroke or embolic event) ( p = 0.002). In multivariable regression, ablation was an independent predictor of the primary composite outcome (hazard ratios, 2.24; 95% confidence interval, 1.09–4.61; p = 0.03). Patients with LVADs referred for endocardial VT ablation had elevated rates of DT and embolic events. Abstract : Supplemental Digital Content is available in the text.